Analisis Biaya Diferensial Dalam Pengambilan Keputusan Membeli Atau Membuat Sendiri Serta Menjual Langsung Atau Mengolah Lebih Lanjut Produk Terasi Pada UD. Sumber Jaya Di Desa Klampis - Safinatun Najah; Purnamawati Purnamawati (Management Department of Economics and Business Of Trunojoyo Madura University, 2023)
Differential cost analysis is used as a tool to measure how much income and costs are incurred if the business owner chooses one alternative decision. Differential costs are costs incurred as a result of selecting certain alternative decisions. Making the right decision will help a business in obtaining maximum profit. The method used is descriptive quantitative. The data used in this study were obtained by direct observation and interviews with business owners. The purpose of this study is to find out the right decision chosen by UD. Sumber Jaya to increase profits. The differential cost analysis used is an alternative decision between buying or making your own and selling directly or processing further. The results of the differential cost analysis show that the right and more profitable decision that can be chosen by business owners is to make their own because the difference in profit is 47% higher than buying from outside suppliers. While the alternative decision to sell directly or process further, the right and more profitable decision that can be chosen by business owners is to process further because the profit earned increases by 87% compared to selling directly.